Diabetes Mellitus and Cognition: Pathway Analysis in the MEMENTO Cohort. (24th August 2021) - Frison, Eric; Proust-Lima, Cecile; Mangin, Jean-Francois; Habert, Marie-Odile; Bombois, Stephanie; Ousset, Pierre-Jean; Pasquier, Florence; Hanon, Olivier; Paquet, Claire; Gabelle, Audrey; Ceccaldi, Mathieu; Annweiler, Cédric; et al.
Abstract : Objective: To assess the role of biomarkers of Alzheimer disease (AD), neurodegeneration, and small vessel disease (SVD) as mediators in the association between diabetes mellitus and cognition. Methods: The study sample was derived from MEMENTO, a cohort of French adults recruited in memory clinics and screened for either isolated subjective cognitive complaints or mild cognitive impairment. Diabetes was defined based on blood glucose assessment, use of antidiabetic agent, or self-report. We used structural equation modeling to assess whether latent variables of AD pathology (PET mean amyloid uptake, Aβ42 /Aβ40 ratio, and CSF phosphorylated tau), SVD (white matter hyperintensities volume and visual grading), and neurodegeneration (mean cortical thickness, brain parenchymal fraction, hippocampal volume, and mean fluorodeoxyglucose uptake) mediate the association between diabetes and a latent variable of cognition (5 neuropsychological tests), adjusting for potential confounders. Results: There were 254 (11.1%) participants with diabetes among 2, 288 participants (median age 71.6 years; 61.8% women). The association between diabetes and lower cognition was significantly mediated by higher neurodegeneration (standardized indirect effect: −0.061, 95% confidence interval: −0.089, −0.032), but not mediated by SVD and AD markers. Results were similar when considering latent variables of memory or executive functioning. Conclusion: In a large clinical cohort in the elderly, diabetes is associated with lower cognition through neurodegeneration, independently of SVD and AD biomarkers.